Radioecological Monitoring And Safety Issues Of The Soil-Water System Of The Zarafshan Oasis - Mukarram Fayzullayeva; Rashid Eshburiyev (Genius Journals, 2025)
This article examines the radioecological state of the soil–water system in the Zarafshan Valley and highlights issues of radiation safety shaped by both natural and anthropogenic factors. The research involved analyzing soil and water samples to determine the composition of radioactive elements, their migration patterns, and bioaccumulation processes. Particular attention was given to assessing potential ecological risks that may affect agricultural land productivity and public health. On the basis of the Zarafshan Valley case study, scientific and practical recommendations were developed to improve the system of radioecological monitoring. The findings of the study hold significant importance for ensuring regional ecological stability, promoting the rational use of natural resources, and strengthening radiation safety.
Keywords: Zarafshan Valley; radioecological monitoring; radiation background